Fibroadenoma versus phyllodes tumor: distinguishing factors in patients diagnosed with fibroepithelial lesions after a core needle biopsy - Cholatip Wiratkapun,; Pawat Piyapan,; Panuwat Lertsithichai,; Noppadol Larbcharoensub (Diagnostic and Interventional Radiology, 2014)

(untitled)
PURPOSEWe aimed to identify factors that might help differentiate phyllodes tumors from fibroadenomas among cases in which a fibroepithelial breast lesion was diagnosed from core needle biopsy (CNB) under imaging guidance. MATERIALS AND METHODSA retrospective review was performed on 213 lesions in 200 patients who had undergone both CNB and excisional biopsy during a four-year period between 2008 and 2011. The final pathology revealed 173 fibroadenomas and 40 phyllodes tumors. The data, including patient characteristics, clinical presentation, and mammography, ultrasonography (US), and pathology findings were analyzed. RESULTSUpon univariable analysis, the factors that significantly helped to identify phyllodes tumors consisted of the presenting symptoms (palpable mass or breast pain), increased size on clinical examination, hyperdense mass on mammogram, and the following three US features: heterogeneous echo, presence of round cysts within the mass, and presence of clefts within the mass. The pathologist’s suggestion of a phyllodes tumor was also helpful. The factors that remained statistically significant upon multivariable analysis consisted of symptoms of breast pain, the presence of clefts on US, the presence of round cysts on US and the pathologist’s favoring of phyllodes tumors from a CNB specimen. CONCLUSIONA multidisciplinary approach was needed to distinguish phyllodes tumors from fibroadenomas in patients who had undergone CNB. US findings (clefts and round cysts), suggestive pathological diagnoses, and clinical symptoms were all useful for the decision to surgically remove the fibroepithelial lesions diagnosed from CNB.